Book review: Complete Contract Law. Authored by André Naidoo. (January 2023) - Todd, Andrea
Complete Contract Law . Authored by André Naidoo, Oxford University Press, Oxford, 2021. pp. 692, £37.99. ISBN 9780198749868.